Laurence Sterne's Textual Commerce - Hardie-Forsyth, A (2020)
Laurence Sterne’s Textual Commerce provides a study of Laurence Sterne as a commercial writer. It demonstrates how his correspondence and transactions with booksellers in York and London, his methods of self-promotion, and his early critical reception as a writer of ‘great oeconomy’ shaped his authorial practice as provisional and, in Thomas Keymer’s terms, open to ‘determination from without’. In examining commercial exigency in relation to Sterne’s authorship between 1759-1768, I combine two areas of enquiry that can appear distinct: studies of writers’ interactions with the book trade, which often appear under the rubric of ‘book history’, and studies of the affinity between ‘fictionality’ and ‘credit’, which often perform at a more abstract conceptual level. I argue that, within Sterne’s career and writings, each illuminates the other: the terms of credit he negotiates with his booksellers mark the precise point at which the material fabrication of his books meets abstract concerns with reputation and value in his fiction.